The impact of consumption values towards intention to visit green hotel in Malaysia / Nur Shakinah Joibi and Sharifah Nurafizah Syed Annuar - Joibi, Nur Shakinah; Syed Annuar, Sharifah Nurafizah (UiTM Cawangan Johor, 2020)
Currently, tourism is moving towards sustainable tourism because this industry poses negative impacts to the environment. The hotel industry consumes and produces many resources such as water, energy and produces waste disposal. Therefore, the environmental friendly services in hotel industry are important. The purpose of this paper is to review past study on the impact of the consumption values towards intentions to visit green hotel in Malaysia. A multi-dimensional measure of consumption values is used to determine which values of consumption are valued by domestic and international tourists. The Theory of Consumption Values (TCV) is employed and modified in this study. The functional value, conditional value, social value, emotional value and epistemic value in this study is expected to have impact on intention to visit green hotel in Malaysia.